The Effect of Internal Control System on the Effectiveness of Lending to PT Bank Perkreditan Rakyat Tanah Laut - Suasri, Eni; Amelia, Noor; Pebriana, Rina; Nurmalina, Radna (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
One of the efforts made by business actors to maintain stability and improve the existence of the business they run through credit applications to credit providers such as banks. Lending activities must be carried out by implementing a good internal control system to avoid bad loans and achieve effective lending. The purpose of this study is to determine the influence of the internal control system in terms of the five indicators, namely the control environment, risk assessment, control activities, information and communication, and monitoring the effectiveness of lending. The data analysis technique uses multiple linear regression tests. The results of the hypothesis test show that risk control and assessment activities have an influence on the effectiveness of lending. While the variables of control, information and communication, and monitoring activities have no effect on effectiveness of lending.